Properties of soluble α-chymotrypsin in neat glycerol and water - Castro, Guillermo Raul (2000)
UV scanning of a-chymotrypsin dissolved in neat glycerol and water showed no significant differences in its spectra at pH 7.8. Fluorescence scanning revealed a strong dependence on pH values (between 5.9 to 10.5) of the maximum wavelength emission in water and no pH-dependence in 99% glycerol supplemented with 1% of appropriate buffers. The profile of a-chymotrypsin activity dissolved in water-glycerol mixtures with phenyl acetate as substrate displayed two maximum: highest peak was found at 100% water, and the second one was observed in 99% glycerol concentration with about 40% of the relative activity. Optimum pH of the soluble a-chymotrypsin in glycerol showed a displacement of 1 pH/U towards the alkaline side compared to water at pH 8.0. Kinetic and thermodynamic analysis using kinetic measurements of the thermal stability of a-chymotrypsin showed a higher inactivation rate in neat glycerol as compared to water in 30 to 45°C range, however, when temperature increases enzyme stability in glycerol is better than water. Thermostability of trypsin and a-chymotrypsin dissolved in glycerol at 100°C showed a half reaction time of approximately 7 and 20 h, respectively, and less than 1 minute in aqueous buffer for both enzymes.